PLANTATION COMMODITY SELECTION IN CENTRAL JAVA USING MABAC METHOD AND PSI WEIGHTING - Nurhaliza, Andini Ayu; Cholil, Saifur Rohman (JURTEKSI (Jurnal Teknologi dan Sistem Informasi), 2025)
Abstract: Central Java has significant potential in the plantation sector with various commodities such as pepper, cloves, tobacco, tea, sugarcane, coffee, nutmeg, and patchouli. However, the abundance of commodities does not guarantee that all of them provide maximum benefits. This study aims to recommend the most potential plantation commodities for development. The research utilizes plantation data from Central Java over the past few years, obtained from Satu Data Indonesia, covering land area, production, productivity, and the number of farmers. The evaluation criteria include land area, production, productivity, and the number of farmers. In the decision-making process, a Decision Support System (DSS) approach is applied using the Multi-Attributive Border Approximation Area Comparison (MABAC) method and the Preference Selection Index (PSI). The MABAC method is used to determine rankings, while PSI is used for criteria weighting. The results indicate that sugarcane, tobacco, and robusta coffee are the best commodities, with final scores of 0.419, 0.237, and 0.020, respectively. Therefore, it can be concluded that the most potential commodities for development in Central Java are sugarcane, tobacco, and robusta coffee. Keywords: central java; MABAC;  plantation; PSI  Abstrak: Jawa Tengah memiliki potensi besar di sektor perkebunan dengan berbagai komoditas seperti lada, cengkeh, tembakau, teh, tebu, kopi, pala, dan nilam. Tetapi dengan banyaknya komoditas, tidak memastikan bahwa semua komoditas memberikan manfaat yang maksimal. Penilitian ini bertujuan membuat rekomendasi komoditas perkebunan yang paling potensial untuk dikembangkan. Penelitian ini menggunakan data perkebunan di Jawa Tengah dalam beberapa tahun terakhir yang diperoleh dari Satu Data Indonesia, mencakup luas lahan, produksi, produktivitas, jumlah petani. Kriteria evaluasi yang digunakan meliputi luas lahan, produksi, produktivitas, jumlah petani. Dalam proses pengambilan keputusan, digunakan metode SPK dengan pendekatan (MABAC) serta (PSI). Metode MABAC digunakan untuk menentukan peringkat, sementara PSI digunakan untuk pembobotan kriteria. Hasil yang diperoleh dari penilitian ini yaitu Tebu, Tembakau, Robusta merupakan tanaman terbaik dengan hasil akhir 0,419, 0,237, 0,020. Oleh karena itu, dapat disimpulkan tanaman yang dapat dikembangkan dengan potensial di wilayah Jawa Tengah dengan berbagai macam komoditas yaitu komoditas Tebu, Tembakau, dan Robusta. Kata kunci: jawa tengah; MABAC; perkebunan ; PSI